The Sound Sensitivity Symptoms Questionnaire Version 2.0 (SSSQ2) as a Screening Tool for Assessment of Hyperacusis, Misophonia and Noise Sensitivity: Factor Analysis, Validity, Reliability, and Minimum Detectable Change - Hashir Aazh; Fatma Betul Kula (Brain Sciences)
Background/Objectives: The Sound Sensitivity Symptoms Questionnaire version 2 (SSSQ2) is a brief clinical tool with six items designed to be used (1) as a measure for severity of sound sensitivity symptoms in general (based on its total score) and (2) as a checklist to screen different forms of sound sensitivity. The objective of this study was to assess the psychometric properties of the SSSQ2. Method: This was a cross-sectional study. A total of 451 people completed the online survey. A total of 154 people completed the survey twice with a two-week interval to establish test–retest reliability. The average age of the participants was 36.5 years (range 18 to 86 years). Results: Confirmatory factor analysis showed that the SSSQ2 is a one-factor questionnaire. Cronbach’s α was 0.80. The test–retest reliability was good for the total SSSQ2 score and was moderate for the sum of items 1 and 3 (indicating loudness hyperacusis), item 2 (for pain hyperacusis), item 4 (for misophonia), item 5 (for fear hyperacusis), and item 6 (for noise sensitivity). The minimum amount of change that constitutes a true change in the total SSSQ2 score is ≥5 points. Conclusions: The SSSQ2 can be used in clinical practice or research setting to measure the severity of general sound sensitivity as a one-factor questionnaire with acceptable internal consistency and good reliability. In addition, the individual items in the SSSQ2 can be used as a checklist to screen for various forms of sound sensitivity.